2017
DOI: 10.5005/jp-journals-10024-2033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Hypochlorite on Push-out Bond Strength of Four Calcium Silicate-based Endodontic Materials when used for repairing Perforations on Human Dentin: An in vitro Evaluation

Abstract: Aim: This study aimed to evaluate the push-out bond strength of NeoMTA Plus (NMTA), EndoSequence root repair material fast set putty (ERRMF), biodentine (BD), and ProRoot white mineral trioxide aggregate (PMTA) when used as perforation repair materials after exposure to 2.5% sodium hypochlorite (NaOCl) during the early setting phase. Materials and methods:Horizontal midroot sections were prepared from single-rooted human teeth. Sections (n = 144) were randomly divided into four groups: PMTA, BD, NMTA, and ERRM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
2
9
1
Order By: Relevance
“…SEM analysis confirmed the presence of unusual needle‐like shaped particles on the BC putty surface and undeveloped globular crystals with a lack of its original hexagonal shape on the BC paste surface when they immersed in NaOCl and CHX. Previous studies reported that NaOCl did not alter the crystalline structure of MTA or BC putty (Alsubait, 2017; Marciano et al, 2015). This feature may be attributed to the surface carbonation of both BC materials when it contacts with either NaOCl or CHX (El‐Turki et al, 2010).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…SEM analysis confirmed the presence of unusual needle‐like shaped particles on the BC putty surface and undeveloped globular crystals with a lack of its original hexagonal shape on the BC paste surface when they immersed in NaOCl and CHX. Previous studies reported that NaOCl did not alter the crystalline structure of MTA or BC putty (Alsubait, 2017; Marciano et al, 2015). This feature may be attributed to the surface carbonation of both BC materials when it contacts with either NaOCl or CHX (El‐Turki et al, 2010).…”
Section: Discussionmentioning
confidence: 89%
“…Meanwhile, the alkalinity of NaOCl could induce surface oxidation that creates consumption and surface degradation. Alsubait (2017) confirmed that NaOCl enhanced the setting reaction, improved the physical properties, preserved the surface morphology, and did not interfere with cubic crystals formation, yet it can lower the amount of crystallization of BC putty.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations